Life cycle assessment of a passive remediation system for acid mine drainage: Towards more sustainable mining activity. (20th February 2019) - Martínez, Natalia Mónica; Basallote, M. Dolores; Meyer, Andreas; Cánovas, Carlos R.; Macías, Francisco; Schneider, Petra
Abstract: Historical mining activity in the Iberian Pyrite Belt has left a huge number of abandoned sites; these cause severe water pollution by acid mine drainage, for which remediation seems to be unaffordable. Although the choice of remediation systems is usually dictated by technical and economic factors, the sustainability of such systems is becoming increasingly important in decision making, and efforts to promote greener remediation measures are being made. Life cycle assessment is a proven methodology that can help in the selection of the best available technology by reducing environmental burdens while ensuring the efficiency of the treatment. The main goal of this study is to perform the first life cycle assessment for dispersed alkaline substrate technology, effective for metal-rich and acid waters, in order to determine the environmental impacts generated throughout its entire life cycle and the factors controlling the environmental performance of this technology. We show that although the construction of the plant initially creates significant environmental impacts, these become negligible within a few years (4.5 years). The results also show that the potential impacts of the plant are closely related to the upstream production chain of the materials employed in this technology. Thus, the replacement of certain material sources and circular usage would lead to a significant decrease in impact values. The replacement of wood chips by forestry waste would reduce emissions by between 50% and 100%. The global warming potential of the plant was 1.86 kg CO2 eq/m 3, to which limestone dissolution contributes 94% of the total value, and hence the replacement of non-carbonate alkaline materials would significantly decrease the emissions to the atmosphere. This study also finds evidence for the lower carbon footprint of passive treatment in comparison with other wastewater treatment systems analyzed using life cycle analysis. The results of this work may contribute to more environmentally friendly mining by providing an insight into environmental burdens related to the available passive treatment options for acid mine drainage during mining operations and the post-closure phases. Graphical abstract: Highlights: LCA methodology is for first time applied to mine water treatment by DAS technology. DAS technology decontaminates mine water using alkaline materials and no energy. Construction impacts are predominant but are attenuated over long operation periods. Replacement of wood chips by forestry wastes reduced the emissions by 50%–100%. The use of carbonate alkaline materials is the main source of carbon emissions.